Effect of pH, rearing temperature and sunlight on infectivity of Malaysian isolate of nucleopolyhedrovirus to larvae of Spodoptera litura (Lepidoptera:Noctuidae) - Sajap, Ahmad Said; Abdul Bakir, Mohammad; Abdul Kadir, Hussan; Abdul Samad, Norani (Cambridge University Press, 2007)
The effects of pH, sunlight and rearing temperature on infectivity of nucleopolyhedrovirus (SpltNPV) were investigated against larvae of Spodoptera litura (Fabricius). The infectivity of virus increased with increased larval rearing temperature. The LT50 values were significantly reduced from 24 to 6 days when rearing temperature was increased from 20 to 35 8C. The pH of the substrate significantly affected the infectivity of the virus. The LT50 values increased to about fourfold when the pH of suspension was raised from 7 to 11. Infectivity of the virus was more adversely affected in alkaline than in acidic suspension. Sunlight also deleteriously affected infectivity of the virus. The LT50 values increased with the increase in the period of sunlight exposure. A complete viral inactivation occurred after 12 h of direct sunlight exposure.